Crisis in digital era and brand sustainability: Analyzing the #whitelabapologize activism on social media - Chasana, Rona Rizkhy Bunga; Purworini, Dian; Apriliani, Riski (Program Studi Ilmu Komunikasi, 2025)
This research aims to examine how crisis information spreads on social media and leads to activism. The public perceives the Whitelab brand event, which collaborated with K-Pop idol Sehun, as fraught with issues. This has resulted in public protests and the emergence of the #whitelabapologize hashtag on Twitter. This qualitative research uses social network analysis (SNA) to understand the social network and actors surrounding the conversation. A total of 10,000 tweets using #whitelabapologize were extracted from Twitter using Netlytic on the crucial date of the event. The research results classify #whitelabapologize as hashtag activism. Individual actors and the fan bases of K-pop idols drive the conversations on this social network. The data also reveals that this activism follows the logic of connective action.